Education or creativity: What matters most for economic performance? - Emanuela Marrocu; Raffaele Paci (European Regional Science Association (ERSA), 2011)
There is a large consensus among social researchers on the positive role played by human capital on economic performances. The standard way to measure the human capital endowment is to consider the educational attainments by the resident population, usually the share of people with a university degree. Recently, Florida (2002) suggested a different measure of human capital - the "creative class" - based on the actual occupations of individuals in specific jobs like science, engineering, arts, culture, entertainment. However, the empirical analyses carried out so far overlooked a serious measurement problem concerning the clear identification of the education and creativity components of human capital. The main purpose of this paper is to try to disentangle this issue by proposing a disaggregation of human capital into three non-overlapping categories of creative graduates, bohemians and non creative graduates. By using a spatial econometric framework to account for spatial dependence, we assess the concurrent effect of the human capital indicators on total factor productivity for 257 regions of EU27. Our main results indicate that the highly educated creative group is the most relevant one in explaining production efficiency, while the other two categories - non creative graduates and bohemians - exhibit negligible effects. Moreover, a relevant influence is exerted by technological capital and by the level of tolerance providing robust evidence that an innovative, open, inclusive and culturally diverse environment is becoming more and more crucial for productivity enhancements.
Keywords: 330